Unusual evolution of the magnetism on oxygen in La1−χSrχCoO3. Issue 2 (4th January 2013) - Medling, Scott; Lee, Y.; Zheng, H.; Mitchell, J. F.; Freeland, J. W.; Harmon, B. N.; Bridges, F.; Stanek, Christopher R.; Nikl, Martin; Kovács, László; Greulich‐Weber, Siegmund
Abstract We present X‐ray absorption spectroscopy (XAS) and X‐ray magnetic circular dichroism (XMCD) data of La1−χSrχCoO3, for χ= 0.10‐0.30, at the O K edge and then compare the results to local density approximation (LDA) and generalized gradient approximation (GGA) calculations using a 2x2x2 supercell. Increases in the XAS and XMCD are nonlinear with χ, instead appearing correlated with the overall system magnetism, which changes from glass‐like to metallic ferromagnetism around χ=0.18. The magnetic states observed in XMCD only occur at the beginning of the pre‐edge; higher energy states show no orbital moment, suggesting two distinct types of holes exist. This is consistent with the formation of ferromagnetic clusters growing with χ and eventually overlapping for χ>0.18. Subsequent LDA and GGA calculations find a significant spin magnetic moment on O atoms (which are spinpolarized) and indicate that the doping‐induced holes are nearly equally distributed over the Co and O atoms. Calculations of the magnetization for individual O sites indicate that they are not all equivalent, but actually have different moments, depending on the proximity to Sr. This variation in the small fraction of oxygen state with angular momentum may explain in part the unusual magnetic behavior of these materials. Further, the orbitally decomposed density of states reveals that the bands from the traditional picture (localized eg and t2g states) overlap considerably and extend from ‐6 to 4 eV around E F, suggesting that the local picture is not the best for La1−χSrχCoO3 (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)